Development of a biomimetic thyroid acellular scaffold as a 3D platform for modeling thyroid cancer aggressiveness and drug resistance - Zhang, Liang; Sun, Rong; Li, Shuheng; Zhang, Peng; Long, Houlong; Liu, Bin; Li, Feng (Frontiers in Bioengineering and Biotechnology, 2025)
Traditional two-dimensional (2D) cell culture models for thyroid cancer research fail to recapitulate the complex tumor microenvironment (TME), leading to a significant gap between preclinical findings and clinical outcomes. To address this limitation, this study focuses on the development and characterization of a novel three-dimensional (3D) tumor model utilizing a thyroid acellular scaffold (TAS) derived from rat tissue. We prepared the TAS through an optimized decellularization protocol, followed by comprehensive histological, biochemical, proteomic, and mechanical evaluations. Human thyroid cancer cells were then seeded onto the TAS, and their biological behaviors, including proliferation, invasion, gene expression, and drug sensitivity to cisplatin and vemurafenib, were systematically compared to conventional 2D cultures. Our results demonstrate that the TAS provides a biomimetic microenvironment, successfully preserving the native extracellular matrix (ECM) architecture, key proteins, and a significant fraction of endogenous growth factors. Compared to 2D cultures, cells within the 3D TAS model exhibited significantly enhanced proliferation and time-dependent invasion. Critically, the 3D microenvironment induced a more aggressive phenotype, characterized by upregulated expression of the BRAF V600E oncogene and the induction of epithelial-mesenchymal transition (EMT), and conferred significantly increased resistance to both cisplatin and vemurafenib. These findings indicate that our tissue-specific, TAS-based 3D model successfully recapitulates key pathophysiological hallmarks of thyroid cancer, representing a more clinically relevant and predictive platform for investigating tumor mechanisms and for the preclinical evaluation of novel therapeutic agents.